The Sensitivity Analysis of Applied General Equilibrium Models: Completely Randomized Factorial Sampling Designs - Harrison, Glenn W.; Vinod, H. D. (The Review of Economics and Statistics, 1992)
Glenn W. Harrison, H. D. Vinod, The Sensitivity Analysis of Applied General Equilibrium Models: Completely Randomized Factorial Sampling Designs, The Review of Economics and Statistics, Vol. 74, No. 2 (May, 1992), pp. 357-362